Effect of Inquiry-based Laboratory Approach on Scientific Process Skills, Critical Thinking Skills, and Opinions of Ninth Grade Students: Cell Unit Example - Basak Erkacmaz, Kubra; Bakirci, Hasan; Kara, Yılmaz (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2023)
This research aimed to investigate the effect of the inquiry-based laboratory approach on the science process and critical thinking skills of 9th-grade students as well as opinions about the approach. The study was designed according to the case study research model. The research was conducted with 56 students, 28 in the experimental group and 28 in the control group, studying at a high school. While the lessons in the experimental group were carried out with the inquiry-based laboratory approach, the subjects were carried out according to the current teaching in the control group. Science Process Skills Test, Critical Thinking Disposition Inventory, and Semi-Structured Interview Form were used as data collection tools. Data were analyzed both through inferential and content analysis. As a result of the research, the inquiry-based laboratory approach effectively improves ninth-grade students' science process skills and critical thinking dispositions. In addition, the inquiry-based laboratory approach enabled students to be successful in subjects such as active participation in the lesson, obtaining permanent information, creating information themselves, group work, and experimenting. An inquiry-based laboratory approach to various topics is recommended, and teachers should be trained in it.